ROLA PRZEDSIĘBIORCY W PROCESIE KREATYWNEJ DESTRUKCJI - Kozłowska, Anna (Wydział Prawa i Administracji UAM, 2008)
Schumpeters concept of creative destruction explains the phenomenon of economic development through an objective and automatically unfolding sequence of events connected with the appearance of new entrepreneurs - innovators, and their influence on the existing enterprises. Innovations take place when traditional production factors find their application in new, modern methods of production, and their consequence is the change o f the existing industrial structure. They are treated as the driving force of the sequence of significant events in which the entrepreneur reforms and revolutionises production patterns through utilising new ideas or new technical possibilities of production of new goods, or producing old” goods using new methods, through opening new sources of resources or new markets for products or through organisational changes in industry. According to J. A. Schumpeter, the entrepreneurs activity, involving the implementation of innovations, is the main source of repeating waves of prosperity, which revolutionise the organism of the economy and recessions, triggered off by the influence of new products and methods disrupting current equilibrium. The aim of the study is a review of J. A. Schumpeters views on the role played by the entrepreneur in the process of economic development, and their gradual evolution caused by institutional changes taking place in the system of a capitalist economy.
THE ROLE OF AN ENTREPRENEUR IN THE CREATIVE DESTRUCTION PROCESS